Desenvolvimento pra quem? Uma análise dos impactos da atuação de uma multinacional brasileira em solo africano - Spohr, Nicole (2016)
The literature of Corporate Social Responsibility (CSR) has been debating for decades the impact of corporations on society. The classic paradigm argues that CSR only pays off if it results in more profits than the possible losses of its non-use. Criticism of this instrumental view culminated in the emergence of the political perspective of CSR, that suggests an extended model of governance, in which companies voluntarily contribute to the welfare of the societies they operate in. Despite the political turn, the CSR research agenda has not been focusing enough on issues relevant to peripheral countries, such as the asymmetries of power between multinational corporations and local governments. As the dimension of power is one of the objects of study of postcolonialism, I argue that this approach can contribute to the discussion of CSR in the global periphery. Therefore, this study aims to answer the following question: how does a semi-peripheral multinational do business on the periphery? In order to answer this question, I investigated the impacts of the operations of a Brazilian multinational in an African country. The fieldwork included 28 in-depth interviews with members of the multinational and the local civil society. In addition, about 2,800 pages of documents were analyzed. The results indicate that if we understand CSR as the impacts of the multinational activities, the resettlement of 5,500 people to make room for the extraction of minerals without corresponding legislation caused the violation of their rights. Another finding includes the multinational management logic, which I have considered colonial. It has included the support of Brazilian diplomacy in order to obtain the right to extract minerals, the relationship with the local government marked by threats and coercion, as well as the construction of African peoples as subaltern compared to their Brazilian peers. The analysis of the CSR actions of the studied corporation indicates that the publication of environmental and social information seems to be used as a way to justify and mitigate the negative impacts of the multinational on the local society. Furthermore, the company seems to impose a Brazilian way of development regardless of what the local society understands as such. Thus, this thesis contributes to the CSR debate by highlighting that the political perspective on CSR does not fully explain the role of the studied multinational in the global periphery, by unveilling the construction of subalternity in terms of race and culture and by proposing the ideia of a hierarchy of subalternities in the global periphery. Finally, this study supports the need to break with the colonial logic in terms of local development.